Transgenic plant generated by RNAi-mediated knocking down of soybean Vma12 and soybean mosaic virus resistance evaluation - Luan, Hexiang (AMB Express, 2020)
Soybean mosaic virus (SMV) is one of the most destructive viral diseases in soybean and causes severe reduction of soybean yield and destroys the seed quality. However, the production of SMV resistant plants by transgenic is the most effective and economical means. Based on our previous yeast two-hybrid assay, the GmVma12 was selected as a strong candidate gene for further function characterization. Here we transformed soybean plants with a construct containing inverted repeat of-GmVma12 sequence to analyze the role of GmVma12 during SMV invasion. Totals of 33 T(0) and 160 T(1) plants were confirmed as positive transgenic plants through herbicide application, PCR detection and LibertyLink(®) strip screening. Based on the segregation ratio and Southern Blot data, T(1) lines No. 3 and No. 7 were selected to generate T(2) plants. After SMV-SC15 inoculation, 41 T(1) and 38 T(2) plants were identified as highly resistant, and their quantification disease levels were much lower than non-transformed plants. The transcript level of GmVma12 in T(2) plants decreased to 70% of non-transformed plants. The expression level of SMV-CP transcript in T(2) transgenic plants was lower than that in non-transformed plants and SMV CP protein in T(2) plants could not be detected by Enzyme-linked Immunosorbent assay, which indicated that SMV production would be inhibited in transgenic plants. Moreover, coat mottles of T(2) seeds were obliterated significantly. In conclusion, inverted repeat of the hairpin structure of GmVma12 interfered with the transcription of GmVma12, which can induce resistance to SMV in soybean. This research lays the foundation for the mechanism of SMV pathogenesis, and provides new ideas for SMV prevention and control.